Effects of wollastonite and phosphate treatments on cadmium bioaccessibility in pak choi (Brassica rapa L. ssp. chinensis) grown in contaminated soils - Guo, Kexin; Zhao, Yuehua; Zhang, Yang; Yang, Jinbo; Chu, Zhiyuan; Zhang, Qiang; Xiao, Wenwei; Huang, Bin; Li, Tianyuan (Frontiers in Nutrition, 2024)
Cadmium (Cd) contamination of soil can strongly impact human health through the food chain due to uptake by crop plants. Inorganic immobilizing agents such as silicates and phosphates have been shown to effectively reduce Cd transfer from the soil to cereal crops. However, the effects of such agents on total Cd and its bioaccessibility in leafy vegetables are not yet known. Pak choi (Brassica rapa L. ssp. chinensis) was here selected as a representative leafy vegetable to be tested in pots to reveal the effects of silicate–phosphate amendments on soil Cd chemical fractions. Three heavy metal-immobilizing agents: wollastonite (W), potassium tripolyphosphate (KTPP), and sodium hexametaphosphate (SHMP) were added to the soil in order to get four different treatment groups i.e. control (CK), application of wollastonite alone (W), wollastonite co-applied with KTPP (WKTPP), application of wollastonite co-applied with SHMP (WSHMP) for remediation of soils with different levels of Cd contamination. All three treatments increased the effective bio-Cd concentration in the soils with varying levels of contamination, except for W under moderate and heavy Cd contamination. The total Cd concentration in pak choi plants grown in mildly Cd-contaminated soil was elevated by 86.2% after WKTPP treatment compared to the control treatment could function as a phytoremediation aid for mildly Cd-contaminated soil. Using an in vitro digestion method (physiologically based extraction test) combined with transmission electron microscopy, silicate and phosphorus agents were found to reduce the bioaccessibility of Cd in pak choi by up to 66.13% with WSHMP treatment. Meanwhile, wollastonite and phosphate treatments may cause Cd to be firmly enclosed in the cell wall in an insoluble form, reducing its translocation to edible parts and decreasing the bioaccessibility of Cd in pak choi. Therefore, this study thus reveals effective strategies for the remediation of soil Cd and the reduction of Cd bioaccessibility in crops based on two indicators: total Cd and Cd bioaccessibility. Our findings contribute to the development of methods for safer cultivation of commonly consumed leafy vegetables and for soil remediation.